Hubungan Karakteristik, Pengetahuan, dan Penggunaan Teknologi Informasi dengan Perilaku Berisiko HIV/AIDS pada Siswa SMA Kristen Eben Haezar Manado - Kandou, Grace D.; Lampus, Benny S.; Hadiwijaya, Reynaldi R. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2013)
Background: HIV/AIDS is a deadly disease, which has become a global issue. The age of 15-24 years is the most vulnerable of contracting HIV/AIDS. Increased use of information technology over the past decade may increase the risk of HIV/AIDS, especially for adolescents. This study aims to see the correlation beÂtween characteristic, knowledge and the use of information technology with high-risk behavior of HIV/AIDS in Eben Haezar Senior High School students. Methods: A cross-sectional survey was conducted on Eben Haezar Senior High School students in Manado. Respondents were 97 people, which were taken from 23 classes. Respondents completed a closed, self-administered questionnaire about their knowledge, use of information technology, and high-risk behavior. Results: A total of 50.5% students had poor knowledge about HIV/AIDS, 55.7% stated they frequently use the information technology, and 13.4% students had high-risk behaviors. Chi-square test showed a correÂlation (p < 0.05) between characteristic and high-risk behavior, knowledge and high-risk behavior, and the use of information technology and high-risk behavior. Conclusions: it was found that male students with poor knowledge about HIV/AIDS, and frequent use of information technology are more likely to have a high-risk behavior. Keywords: HIV/AIDS, adolescents, student, characteristic, knowledge, information technology, high-risk behavior